Law and psychiatry—current and future perspectives - Steinert, Tilman; Henking, Tanja (Frontiers in Public Health, 2022)
We describe relevant interfaces between law and psychiatry and current ethical and legal views and changes within the past decades. Ideas of patient autonomy and patients' rights have been major drivers of changes in legal frameworks. We describe developments in the areas of patient information and informed consent, involuntary placement and involuntary treatment, use of coercive measures, forensic psychiatry, digital mental health, data privacy, physician liability, suicide, assisted suicide, euthanasia, end of life decision-making, advance directives, legal and illegal drugs, and delegation and substitution of professional activities. There is no unidirectional pathway between law and ethics. Views, conflicts, and requirements differ between countries and within countries and will need to be balanced according to the societies' changing values also in the future.